Qualidade de vida de docentes do ensino superior de um centro universitário - Silva, Ivone Corsi da; Portes, Leslie Andrews; Mendes, Gelton Novaes (Journal of Interdisciplinary Lifestyle Studies, 2016)
O presente estudo, de natureza descritiva e analítica, com abordagem quantitativa, objetivou avaliar a Qualidade de Vida (QV) de 312 docentes de ensino superior de um Centro Universitário denominacional e confessional. Os aquiescentes foram 35 docentes (11%) submetidos ao questionário autoadministrado e resumido de Qualidade de Vida da Organização Mundial da Saúde (WHOQOL-Bref.). Os resultados foram submetidos à análise descritiva. A QV Global alcançou (média ± desvio-padrão) 72,0 ± 9,7 pontos, sendo avaliada como satisfatória. Nos Domínios Físico, Psicológico, Relações Sociais e Meio Ambiente, os escores foram, respectivamente, 72.6 ± 14,5, 75,0 ± 12,0, 71,4 ± 16,8 e 69,2 ± 12,7 indicando também percepções satisfatórias. Quality of Life of Faculty in Higher Education The aim of this study, from a descriptive and analytical nature, in a quantitative approach, was to evaluate the Quality of Life (QOL) of 312 professors from a denominational and confessional University, in their physical, psychological, social relations and environment aspects. The respondents were 35 professors who self-administered WHOQOL-bref questionnaire. Results were submitted to a descriptive analysis using the statistical package GraphPad Prism version 6.0 forWindows (www.graphpad.com). Distribution of data was assessed by D’Agostino & Pearson test. Data are presented as means ± standard deviations. Global QOL was 72.0 ± 9.7. In the areas of Physical, Psychological, Social Affairs and the Environment, QOL was, respectively, 72.6 ± 14.5, 75.0 ± 12.0, 71.4 ± 16.8 and 69.2 ± 12.7. The QOL of the university professors was perceived as good to very good. These results are similar to other studies.